Innovation pathways and trajectories in India's auto component industry - Rajnish Tiwari; Katharina Kalogerakis (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2017)
India's automotive sector has grown tremendously in the post-liberalization period. The growing domestic market, increased export opportunities and greater emphasis of vehicle manufacturers on high-quality, innovative solutions have created a context for component suppliers to ramp up their innovation capabilities as well. For about past 20 years the auto component industry has consistently acted as a key enabler of various frugal vehicles launched in India. Our multi-level and multi-approach study, making use of firm and sector-level data while combining case studies with expert interviews, seeks to investigate the prevalent innovation pathways and trajectories in India's Auto Component Industry. The results indicate that firms often engage in designing and developing components making use of modern, digital technologies, and manage to reach very high levels of process and resource efficiency. The huge domestic market, and the rising global demand, for affordable, high quality products provide good incentives for investments and openness for external knowledge. Cooperation between Indian and global companies as well as mergers and acquisitions have accelerated the development of innovation capabilities in India. The focused approach on developing concrete applications within requisite parameters gives rise to "appropriate solutions" that balance economic, ecological and technological performance. The study discovered a remarkable set of innovation pathways that makes use of collaborative development, avoids over-engineering and is often driven by economies of scale. All this is also stimulated by the state that developed into a key promoter of innovations.
Keywords: 330; Innovation Pathways; Innovation Trajectories; Automotive; Auto-Components; India